Use of Design Criteria for Intermediate Languages - Madsen, Ole Lehrmann; Kristensen, Bent Bruun; Staunstrup, Jørgen (DAIMI Report Series, 1976)
A number of design criteria for intermediate languages are proposed. The intermediate language is viewed as an interface between the (syntax) analysis and the synthesis (code generation). To illustrate the ideas we propose an intermediate language for an existing high level language. The translation from the source language to the intermediate language is defined formally by an affix translation grammar.